Towards Rabies Elimination in Pakistan: Barriers, Facilitators, and the Role of One Health - Anum Shaikh; Shifa Salman Habib; Ali Faisal Saleem; Naseem Salahuddin (Journal of Epidemiology and Global Health)
Abstract Background Rabies is a neglected zoonotic disease with an estimated 59,000 deaths annually, disproportionately affecting low- and middle-income countries. Pakistan remains a high-burden setting due to weak surveillance, poor intersectoral coordination, and limited public awareness. Therefore, this study aimed to examine the barriers and facilitators to rabies control in Pakistan through the One Health approach, integrating perspectives from both community members and institutional stakeholders. Methods This mixed-methods study design was conducted in Karachi, where 385 household respondents completed a structured Knowledge, Attitudes, and Practices (KAP) survey, and 10 stakeholders (out of 14 approached) were interviewed across human, animal, and environmental sectors. The survey tool was adapted from previously validated instruments and pilot-tested. Thematic analysis was conducted using a deductive framework based on One Health principles. The quantitative data were analyzed descriptively using IBM SPSS Statistics 21, whereas the qualitative data were analyzed using Atlas.ti. Results The average knowledge score was 5.54 out of 13 (42.6%), indicating substantial knowledge gaps among community members. Key barriers identified included limited vaccine availability, inadequate surveillance systems, fragmented dog population control, and weak multisectoral collaboration. Enabling factors included stakeholder willingness, local Trap-Neuter-Vaccinate-Release (TNVR) initiatives, and existing collaborative frameworks. Stakeholder awareness of the One Health approach was present but lacked institutional translation. Conclusion A coordinated, One Health-based strategy for rabies elimination is urgently needed in Pakistan that addresses both systemic and community-level gaps through sustained advocacy, stronger intersectoral coordination, expansion of TNVR initiatives, and establishment of centralized surveillance for bite incidents and post-exposure management.